Correlation Between Magnesium and HbA1C in Type 2 Diabetes Mellitus - Makaju, Hari Sharan; Sharma, Vijay Kumar; Yadav, Binod Kumar; Tuladhar, Eans Tara; Bhandari, Roshan; Bhattarai, Aseem; Raut, Mithileshwor; Dubey, Raju Kumar; Niraula, Apeksha; Sapkota, Alisha; et al. (Nepalese Medical Journal, 2024)
Background: Magnesium (Mg) is most abundant electrolyte with unlimited physiologic importance in the body, playing a vital role in many fundamental processes. Cellular magnesium is an essential cofactor for various enzymes involved in glucose transport, insulin release and glucose oxidation. Mg has potential role in improving insulin sensitivity and preventing diabetes and its complications. Hypomagnesemia promotes to the initiation and progression of DM and its macrovascular and microvascular complications. Objectives: The aim of this study was to evaluate the correlation of magnesium with HbA1C in T2DM. Material and Methods: This cross sectional study conducted at Tribhuvan University Teaching Hospital, included 85 diagnosed with type 2 diabetes Mellitus visiting Medicine OPD and 85 apparently healthy controls. Clinical and anthropometric characteristics were documented using clinical proforma. The fasting blood samples were collected for estimating serum glucose, HbA1C and magnesium. Results: The mean values of BMI, FBG, HbA1C were found to be significantly elevated in T2DM, but that of Mg were higher in healthy controls (p<0.05). The prevalence of hypomagnesemia in T2DM was found to be 32.94%. The Serum magnesium levels were moderate negatively correlated (r = -0.544, P<0.001) with HbA1C. Conclusion: Patient with Type 2 Diabetes Mellitus showed significantly low magnesium levels compared to heathy controls as well as uncontrolled HbA1C levels also showed significantly low magnesium level than controlled HbA1C level. There was significant inverse correlation between serum Mg level and HbA1C level in patients with T2DM. So if serum magnesium values are made to rise, HbA1C values will fall.